How Would Hedge Fund Regulation Affect Investor Behavior? Implications for Systemic Risk - Naoaki Minamihashi; Naoki Wakamori (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2014)
We estimate an investors' demand model for hedge funds to analyze the potential impact of leverage limits in the industry. Our estimation results highlight the importance of heterogeneous investor preference for the use of leverage, i.e., 20% of investors prefer leverage usage while others do not. We then conduct a policy simulation in which regulators put a cap on allowable leverage, as proposed by the Financial Stability Board in 2012. Simulation results suggest that the 200% leverage limit would lower the total demand (assets under management) for hedge funds by 10%. In particular, the regulation would lead to lower investments in highly leveraged funds and to lower investments in risky strategies, which, in turn, would reduce systemic risk.
Keywords: G38; G23; L52; 330; hedge funds; demand estimation; leverage; regulation; systemic risk